2019
DOI: 10.1680/jenhh.19.00006
|View full text |Cite
|
Sign up to set email alerts
|

Static behaviour of a two-tiered Dou-Gong system reinforced by super-elastic alloy

Abstract: The Dou-Gong system in Asian timber structures plays an important role in resisting seismic action. Traditional carpentry in Asia uses timber pegs to connect components, which enables relative movement between components and hence provides friction to dissipate energy in an earthquake. This method, however, has some shortcomings, such as inadequate stiffness to resist a large lateral force, and, therefore, the structures tend to exhibit permanent deformation after earthquakes. This study proposes a new techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…One method to enlarge the damping ratio is to prestrain the SMA bar. According to one of our previous studies, 51 the damping ratio of the SMA bar can be increased by prestraining it. The TMD can be designed to contain both prestrained and non‐prestrained SMA bars so as to increase the damping ratio of the TMD.…”
Section: Resultsmentioning
confidence: 94%
“…One method to enlarge the damping ratio is to prestrain the SMA bar. According to one of our previous studies, 51 the damping ratio of the SMA bar can be increased by prestraining it. The TMD can be designed to contain both prestrained and non‐prestrained SMA bars so as to increase the damping ratio of the TMD.…”
Section: Resultsmentioning
confidence: 94%
“…To enhance the damping ratio under heating, the SMA can be installed in a pre-strained form. In our previous studies [35,42], experiments showed that pre-strained SMAs can significantly increase the damping ratio. This solution ensures the SMA has sufficient damping.…”
Section: Discussion and Future Extensionsmentioning
confidence: 93%
“…In detail, Yeo et al [17] studied the seismic behaviour of Taiwanese timber brackets subjected to out-of-plane loading, and the effect of their mechanical behaviour-such as failure modes-on the strength of the mechanical model. Xie et al [18] studied the static behaviour of a two-tiered Dou-Gong system reinforced with super-elastic alloy, and found that the pre-strain of the super-elastic alloy can significantly increase the damping ratio in the structure. Previous studies [19][20][21][22] tried to evaluate the mechanical properties and safety state of an entire timber structure through finite element modelling, mathematical methods, and a shakingtable test.…”
Section: History and Research Of Chinese Traditional Structuresmentioning
confidence: 99%